2011
DOI: 10.1002/j.2050-0416.2011.tb00442.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Hopping on Formation of Carbonyl Compounds During Storage of Beer

Abstract: Improving beer flavour stability is an important brewing goal. Pilot scale brewing trials (50 L) were performed that focused on the determination of the influence of hop pellet dosage and dosage timing on carbonyl compounds in stored beer. The reducing activity of experimental worts, beers and stored beers appeared to depend on the hop pellet dose. Brews with lower amounts of hop antioxidants showed an enhanced formation of carbonyl compounds over the course of beer storage. A correlation between DPPH reducing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 20 publications
2
20
0
3
Order By: Relevance
“…V minulosti se studium polyfenolových sloučenin soustřeďovalo zejména na jejich roli v procesu tvorby polyfenol-bílkovinných komplexů, a tím i na vliv polyfenolů na koloidní stabilitu piva (McMurrough et al, 1996a;McMurrough et al, 1996b;Parker, 2007, Aron a Shellhammer, 2010Rehmanji et al, 2005) a možnosti selektivního odstraňování prekursorů vzniku zákalu (Leiper et al, 2005). Po zavedení moderních stabilizačních postupů, schopných odstranit z piva velkou část polyfenolů, byla tato problematika poměrně dlouhou dobu považována za vyřešenou a pozornost se posunula směrem k antioxidačním vlastnostem polyfenolů (Rice-Evans et al, 1996;Pietta, 2000; Dvořáková et al, 2008a), ať už s ohledem na tvorbu senzoricky nežádoucích produktů, zejména karbonylů (Vandehaegen et al, 2006;Mikyška et al, 2011) The aim of this study was to find differences in the quantity and presence of selected polyphenolic substances in barley grown in the Czech Republic and in the People's Republic of China. The barley samples from China had a higher total amount of the polyphenols studied and a significantly higher amount of some specific groups of polyphenols.…”
Section: Porovnání čEských a číNských Odrůd Ječmene S Ohledem Na Techunclassified
See 1 more Smart Citation
“…V minulosti se studium polyfenolových sloučenin soustřeďovalo zejména na jejich roli v procesu tvorby polyfenol-bílkovinných komplexů, a tím i na vliv polyfenolů na koloidní stabilitu piva (McMurrough et al, 1996a;McMurrough et al, 1996b;Parker, 2007, Aron a Shellhammer, 2010Rehmanji et al, 2005) a možnosti selektivního odstraňování prekursorů vzniku zákalu (Leiper et al, 2005). Po zavedení moderních stabilizačních postupů, schopných odstranit z piva velkou část polyfenolů, byla tato problematika poměrně dlouhou dobu považována za vyřešenou a pozornost se posunula směrem k antioxidačním vlastnostem polyfenolů (Rice-Evans et al, 1996;Pietta, 2000; Dvořáková et al, 2008a), ať už s ohledem na tvorbu senzoricky nežádoucích produktů, zejména karbonylů (Vandehaegen et al, 2006;Mikyška et al, 2011) The aim of this study was to find differences in the quantity and presence of selected polyphenolic substances in barley grown in the Czech Republic and in the People's Republic of China. The barley samples from China had a higher total amount of the polyphenols studied and a significantly higher amount of some specific groups of polyphenols.…”
Section: Porovnání čEských a číNských Odrůd Ječmene S Ohledem Na Techunclassified
“…This matter was considered as solved with the introduction of modern stabilization methods able to remove a large part of the polyphenols. Lately, the antioxidation properties of polyphenols gained interest (Rice-Evans et al, 1996;Pietta, 2000;Dvořáková et al, 2008a), particularly with regard to the formation of sensory undesirable compounds (Vandehaegen et al, 2006;Mikyška et al, 2011) as well as anticancerogenic properties of polyphenols (Gerhäuser, 2005;Ramos, 2007). Moreover, the advanced analytical methods enabled the identification and a precise quantification of particular polyphenols (Dvořáková et al, 2008b).…”
mentioning
confidence: 99%
“…Other antioxidants native to the raw materials of beer include ferulic acid 159 , colouring agents including Maillard reaction products 148 and polyphenols 5 . It has been reported that the mode of hopping is very significant in respect of the delivery of hop antioxidants into beer 103 . It has even been suggested that adding hop leaves to the brew kettle can suppress radical formation 60 .…”
Section: Flavour Instabilitymentioning
confidence: 99%
“…Obsah celkových polyfenolů ve chmelu je přibližně 2 až 6 %, množství a složení polyfenolových látek závisí na odrůdě chmele (Lermusieau et al 2001, Mikyška et al 2008, Forster et al 2002. Polyfenolové látky chmele ovlivňují antioxidační aktivitu piva, někte-rými autory byl prokázán i jasný vztah k tvorbě aldehydů staré chuti a senzorické stabilitě piva (Boivin 2008, Dostálek, Karabín 2007, Mikyška et al 2011, Mikyška et al 2010, Forster 2007. Použití chmele významně snižuje tvorbu Streckerových aldehydů v průběhu skladování piva v porovnání s pivem uvařeným bez chmele (Methner et al 2007).…”
Section: Abstract: Antioxidants Hop Storage Polyphenols Beer Flavunclassified
“…Hop polyphenols affect antioxidant activity of beer. Apparent relationship between aldehydes formation and sensorial stability of beers was demonstrated by some autors (Boivin 2008, Dostálek, Karabín 2007, Mikyška et al 2011, Mikyška et al 2010, Forster 2007. Use of hops significantly reduces formation of Strecker aldehydes during storage of beer compared to a beer brewed without hops (Methner et al 2007).…”
Section: Analýzymentioning
confidence: 99%